Fintech and Impulse Buying: How Payment Technology is Changing the Shopping Behavior of Young People in Cirebon - Budi Rusdian; Rita Kusumadewi; Atiatul Maollah; Arphandee Hasan (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: This study evaluates the impact of payment technology, such as fintech payments, on how young people shop and on the rise of impulse purchases, given its convenience. This research aims to explore how fintech payments contribute to market growth and stability.Methods: This study employed a quantitative approach, using SEM analysis, with a sample of 100 respondents. The SmartPLS programs were used to analyze the data collected for this study. Convergent validity was examined using outer loading and AVE, and Cronbach's Alpha and Composite Reliability (rho_a and rho_c) were used as indicators of internal consistency. This study also utilized a literature review approach and examined the impact of fintech payments and impulse buying on the consumption behavior of young people.Results: The results showed that fintech payment and impulse buying positively and significantly affected consumptive buying partially and simultaneously. Fintech payments have a very small influence on consumer behavior, while credit card use has the greatest impact.Conclusion and suggestion: This study showed that many young people remain unaware of the consequences of the conveniences they enjoy, and that these conveniences inevitably come with sacrifices. It is suggested that young people, especially in Cirebon city, be educated in financial literacy and financial management.